(untitled) (Research, Society and Development, 2025)
Exploratory celiotomy is a surgical procedure used to treat various intra-abdominal pathologies in veterinary medicine, and is extremely common, especially in cases of gastrointestinal foreign bodies. In the context of wild animal veterinary medicine, the need for surgical interventions has become increasingly frequent due to the often incorrect handling of these animals. Enterotomy, which consists of incising the intestine to remove foreign bodies or treat obstructions, can be performed through exploratory celiotomy, allowing direct evaluation and intervention in the gastrointestinal tract. This study aims to report a clinical surgical case of a foreign body in a Piranga tortoise, removed by celiotomy and enterotomy after an attempt to eliminate it by enema, in addition to addressing aspects related to radiography, anesthesia and the animal’s postoperative period.